2014
DOI: 10.1371/journal.pone.0096834
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Low-Level Perceptual Networks Related to Clinical Severity in PTSD after an Earthquake: A Resting-State fMRI Study

Abstract: BackgroundSeveral task-based functional MRI (fMRI) studies have highlighted abnormal activation in specific regions involving the low-level perceptual (auditory, visual, and somato-motor) network in posttraumatic stress disorder (PTSD) patients. However, little is known about whether the functional connectivity of the low-level perceptual and higher-order cognitive (attention, central-execution, and default-mode) networks change in medication-naïve PTSD patients during the resting state.MethodsWe investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
68
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(79 citation statements)
references
References 65 publications
(78 reference statements)
11
68
0
Order By: Relevance
“…The SMN has been found related to motor skill learning in animal and human motor control studies ; motor skill learning is accompanied by changes in the connectivity between the SMN and other brain networks associated with the motor function . Consistent with previous studies, Shang et al found a changed spontaneous FC in the SMN using independent component analysis. Whalley et al also suggested that flashbacks in PTSD are correlated with activation in the motor areas, which suggests that flashbacks are a form of memory facilitating action on the environment (e.g., fight‐or‐flight response).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…The SMN has been found related to motor skill learning in animal and human motor control studies ; motor skill learning is accompanied by changes in the connectivity between the SMN and other brain networks associated with the motor function . Consistent with previous studies, Shang et al found a changed spontaneous FC in the SMN using independent component analysis. Whalley et al also suggested that flashbacks in PTSD are correlated with activation in the motor areas, which suggests that flashbacks are a form of memory facilitating action on the environment (e.g., fight‐or‐flight response).…”
Section: Discussionsupporting
confidence: 64%
“…Whalley et al also suggested that flashbacks in PTSD are correlated with activation in the motor areas, which suggests that flashbacks are a form of memory facilitating action on the environment (e.g., fight‐or‐flight response). The increased FC of the motor cortex has also been suggested to represent a brain correlate of preparation for reacting with a physical threat , which is compatible with the psychobiological foundation underlying PTSD . However, LIM regions including the orbitofrontal cortex (OFC) and temporal pole have been widely reported in studies of PTSD and are involved in the reappraisal of emotional processing.…”
Section: Discussionmentioning
confidence: 96%
“…Not significant in the analysis without the studies of (Zhong and co‐workers) and (Shang and co‐workers), which used ReHo and ICA, respectively. Instead, the culmen of the cerebellum became significant (MNI xyz coordinates = 30, −54, −18, cluster volume = 152 mm 3 ).…”
Section: Resultsmentioning
confidence: 92%
“…Remarkably, calligraphy therapy was also effective in reducing hyperarousal symptoms among child survivors in Wenchuan earthquake (Z. Zhu et al, 2014). …”
Section: Chinese Medicinementioning
confidence: 99%